Low-frequency waves in space plasmas - Keiling, Andreas; Lee, Dong-Hun; Nakariakov, V. M. (Valery M.) (Hoboken, NJ : John Wiley and Sons, Inc., 2016)
Low-frequency waves in space plasmas have been studied for several decades, and our knowledge gain has been incremental with several paradigm-changing leaps forward. In our solar system, such waves occur in the ionospheres and magnetospheres of planets, and around our Moon. They occur in the solar wind, and more recently, they have been confirmed in the Sun s atmosphere as well. The goal of wave research is to understand their generation, their propagation, and their interaction with the surrounding plasma. This book presents a concise and authoritative up-to-date look on where wave research stands: What have we learned in the last decade? What are unanswered questions?
Includes index.
Online resource; title from PDF title page (EBSCO, viewed March 30, 2016).
Keywords: Space plasmas; SCIENCE / Astronomy; Space plasmas; Electronic books